What Did We Learn From Plant Growth-Promoting Rhizobacteria (PGPR)-Grass Associations Studies Through Proteomic and Metabolomic Approaches? - Alberton, Dayane; Valdameri, Glaucio; Moure, Vivian Rotuno; Monteiro, Rose Adele; Pedrosa, Fabio de Oliveira; Müller-Santos, Marcelo; de Souza, Emanuel Maltempi (Frontiers in Sustainable Food Systems, 2020)
Plant growth stimulation by microorganisms that interact in a mutually beneficial manner remains poorly understood. Understanding the nature of plant-bacteria interactions may open new routes for plant productivity enhancement, especially cereal crops consumed by humans. Proteomic analyses are particularly useful for elucidating these mechanisms. A complete depiction of these mechanisms will prompt researchers to develop more efficient plant-bacteria associations. The success of microorganisms as biofertilisers may replace the current massive use of chemical fertilisers, mitigating many environmental and economic issues. In this review, we discuss the recent advances and current state of the art in proteomics studies involving grass-bacteria associations. We also discuss essential subjects involved in the bacterial plant-growth promotion, such, nitrogen fixation, plant stress, defence responses and siderophore production.